Hubungan Pijat Bayi terhadap Peningkatan Berat Badan Bayi Usia 0-6 Bulan - Lutfitasari, Ariyani; Hidayati, Fitri; Kusumawati, Erna; Nur Damayanti, Fitriani (STIKes Hamzar, 2024)
Baby massage is a health care for babies with touch therapy with certain techniques. Many studies show that massage in babies provides huge benefits on the baby's development, both physically and emotionally. Baby massage can be used to reduce the number of pain in babies and optimize the growth and development of babies. Objective: To determine the relationship between infant massage and weight gain in infants aged 0-6 months at Fifa Care Moms Kids & Baby Spa, Penawangan Village, Grobogan Regency in 2023. This study was conducted using a quantitative method and was designed as a case control study. An observation approach was used to compare the case group and the control group. All babies were collected at the Fifa Care Moms Kids & Baby Spa in Penawangan Village, Grobogan Regency, from December 2023 to January 2024. The random sampling method was used to divide 30 respondents into two groups: fifteen infants in the intervention group and fifteen infants in the control group. Results: Babies aged 0-6 months who are massaged regularly and get enough breast milk can increase their weight. There was a relationship between regular massage and infant weight gain (p-value = 0.000) with a value of α = 0.05. There is a relationship between giving baby massage to increase the weight of babies aged 0-6 months.